2016
DOI: 10.3389/fmicb.2016.00934
|View full text |Cite
|
Sign up to set email alerts
|

SLPW: A Virulent Bacteriophage Targeting Methicillin-Resistant Staphylococcus aureus In vitro and In vivo

Abstract: Staphylococcus aureus (S. aureus) is a Gram-positive pathogen causing a variety of infections in humans and animals. Extensive use of antibiotics has led to the emergence of methicillin-resistant S. aureus (MRSA). As an alternative antibacterial agent against drug-resistant S. aureus, a lytic phage, designated SLPW, was isolated from fecal sewage in a pig farm. The SLPW was morphologically classified under Podoviridae and contains a double-stranded DNA genome. The genome of SLPW was 17,861 bp (29.35% G+C) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 39 publications
9
78
0
4
Order By: Relevance
“…Results from this study show that the isolated phages were thermally active even at 40°C, 50°C, and 60°C and phages remaining viable up to 60°C after 90 min of incubation. The maximum infectivity was observed at 37°C, and the least infectivity was found at 60°C (Kęsik-Szeloch et al, 2013; Piracha et al, 2014; Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study show that the isolated phages were thermally active even at 40°C, 50°C, and 60°C and phages remaining viable up to 60°C after 90 min of incubation. The maximum infectivity was observed at 37°C, and the least infectivity was found at 60°C (Kęsik-Szeloch et al, 2013; Piracha et al, 2014; Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the release of filamentous Pf Pseudomonas phage was also associated with reduced lung injury and lower cytokine levels [39]. Wang et al demonstrated that phage therapy of uninfected mice does not alter the cytokine levels and significantly lowers those levels during therapy in infected mice, attenuating inflammation caused by S. aureus [40]. Similar findings were reported by Pabary et al, whose data indicate that phage administration reduced inflammation in a murine model of lung infection, lowering inflammatory cytokine and neutrophils levels in bronchoalveolar lavage fluid [41].…”
Section: • Phages and Inflammationmentioning
confidence: 99%
“…As a potential alternative or complement to current antimicrobial agents (i.e., antibiotics), phage therapy has been drawing more and more attention as a strategy to treat MRSA infections (12,13). The potent bactericidal effect of phages is mainly attributed to their genome-encoded cell wall hydrolase, also called lysin, which exhibits a lethal effect by forming holes in the cell wall through peptidoglycan digestion (14).…”
mentioning
confidence: 99%